KOMPARASI KINERJA KEUANGAN ANTARA KELOMPOK PERUSAHAAN BERTIPOLOGI PROSPECTOR DAN DEFENDER PADA EMITEN SEKTOR MANUFAKTUR DI BURSA EFEK INDONESIA - Felicia Barlian (Universitas Mercu Buana, 2015)
Abstract. The objective of this research in to examine the difference of financingperformance between prospector and defender firms. Four variable used as performancemeasures as follows : income growth, sales growth, return on investment, and return on sales.Life cycle theory is used to analyze the difference between from financing performancemeasures. Four variables are used to determine prospector and defender firms : the ratio ofemployees to sales, the price-to-book value ratio, the ratio of capital expenditure to marketvalue equity, and the ratio of capital expenditures to total asset. Based on common factoranalysis and the four other variables, 109 prospector and 109 defender firms are derived frommanufacturing companies listed at Indonesian Stock Exchange from 2011 until 2014. Data ofthis research are analyzed using Mann-Whitney U Test. The results showed that each variableand proxies that are used will be shown mixed results depending on the circumstances ,conditions and organizational strategies used by these companies.Keywords: prospector, defender, life cycle theory, financial performance